A qualitative study on the impact of death during COVID-19: Thoughts and feelings of Portuguese bereaved adults - Aguiar, Ana; Pinto, Marta; Duarte, Raquel (PloS one, 2022)
As a global threat, the COVID-19 pandemic has been an important factor in increasing death rate worldwide. As the virus spreads across international borders, it causes severe illness, death, and disruptions in our daily lives. Death and dying rituals and customs aid bereaved people in overcoming their grief. In this sense, the purpose of this study was to access thoughts and feelings of Portuguese adults and the impact of the loss in daily life during COVID-19. A structured online questionnaire was applied (snowball sampling) and qualitative data on death and mourning namely the impact of the loss in daily life, was collected. One hundred and sixty-six individuals have lost someone since the beginning of the pandemic and were included. Analysis was inspired by Braun and Clark’s content analysis. Most participants were female (66.9%), the median age was of 37.3 years, and 70.5% had a high education degree. Moreover, 30.7% of the participants present anxiety symptoms and 10.2% depression symptoms. The answers of studied participants gave insights on the extent of the loss in day-to-day life and four thematic themes were found: (1) The perceived inadequacy of the funeral rituality, (2) Sadness, fear and loneliness, (3) Changes in sleeping and concentration and increased levels of anxiety and (4) Concerns regarding the pandemic situation. We found a high prevalence of anxiety and depression symptoms in the study sample. Also, the changes in post mortem procedures, have shown to be of great importance in the mourning procedure of the participants.